2023
DOI: 10.1002/ps.7855
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐resistance, inheritance and biochemical mechanism of abamectin resistance in a field‐derived strain of the citrus red mite, Panonychus citri (Acari: Tetranychidae)

Xun‐Yan Liu,
Ke Li,
Deng Pan
et al.

Abstract: BACKGROUNDThe citrus red mite, Panonychus citri (McGregor), a global pest of citrus, has developed different levels of resistance to various acaricides in the field. Abamectin is one of the most important insecticides/acaricides worldwide that target a wide number of insect and mite pests. The evolution of abamectin resistance in P. citri is threatening the sustainable use of abamectin for mite control.RESULTSThe abamectin resistant strain (NN‐Aba), derived from a field strain NN by consistent selection with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…18,[39][40][41] The evaluation of insecticide resistance is thought to be associated with a fitness cost in the absence of pesticide exposure. 42 It has been suggested that these fitness costs of insects be measured by quantitative determination of resistance, cross-resistance or reversion of resistance, suppression of insecticide synergists, inheritance by offspring, and other metrics, 43,44 such as related research on Drosophila melanogaster, 42 Panonychus citri, 45 Bemisia tabaci 46 and Nilaparvata lugens. 47 Although numerous studies have focused on unidirectional factors related to insecticide resistance in Liriomyza spp., the interaction and comprehensive effects of other factors have been largely ignored.…”
Section: Introductionmentioning
confidence: 99%
“…18,[39][40][41] The evaluation of insecticide resistance is thought to be associated with a fitness cost in the absence of pesticide exposure. 42 It has been suggested that these fitness costs of insects be measured by quantitative determination of resistance, cross-resistance or reversion of resistance, suppression of insecticide synergists, inheritance by offspring, and other metrics, 43,44 such as related research on Drosophila melanogaster, 42 Panonychus citri, 45 Bemisia tabaci 46 and Nilaparvata lugens. 47 Although numerous studies have focused on unidirectional factors related to insecticide resistance in Liriomyza spp., the interaction and comprehensive effects of other factors have been largely ignored.…”
Section: Introductionmentioning
confidence: 99%
“…citri is easy to develop acaricide resistance. , In addition, frequent and long-term use of acaricides accelerated the development of P. citri resistance to various acaricides in the field. , According to the arthropod pesticide resistance database (), the resistance cases of P. citri were second only to Tetranychus urticae and Panonychus ulmi in the Tetranychidae family.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In addition, frequent and long-term use of acaricides accelerated the development of P. citri resistance to various acaricides in the field. 7,8 According to the arthropod pesticide resistance database (https://www.pesticideresistance.org/index.php), the resistance cases of P. citri were second only to Tetranychus urticae and Panonychus ulmi in the Tetranychidae family. To prolong the service life of existing acaricides, the resistance mechanism of acaricides in the mite needs to be elucidated.…”
Section: Introductionmentioning
confidence: 99%